Leucocyte-Rich Platelet-Rich Plasma Treatment of Gluteus Medius and Minimus Tendinopathy: A Double-Blind Randomized Controlled Trial With 2-Year Follow-up. Issue 5 (April 2019) - Fitzpatrick, Jane; Bulsara, Max K.; O'Donnell, John; Zheng, Ming Hao
Background: A previously published trial showed that patients with chronic gluteal tendinopathy achieved greater clinical improvement at 12 weeks when treated with a single platelet-rich plasma (PRP) injection than those treated with a single corticosteroid injection (CSI). Purpose: This follow-up study was conducted to determine whether there would be a sustained long-term difference in the modified Harris Hip Score (mHHS) at 2 years for a leucocyte-rich PRP (LR-PRP) injection in the treatment of chronic gluteal tendinopathy. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: This trial included 80 patients randomized 1:1 to receive LR-PRP or CSI intratendinously under ultrasound guidance. Patients had a mean age of 60 years, a 9:1 ratio of women to men, a mean body mass index of 27, and a mean length of symptoms >15 months. No patients had full-thickness tears of the gluteal tendons. An open-labeled extension allowed patients to receive crossover treatment after 3 months. The main outcome measure was the mHHS. Results: The mean mHHS improved significantly at 12 weeks in the PRP group (74.05; SD, 13.92) as compared with the CSI group (67.13; SD, 16.04) ( P = .048). At 24 weeks, the LR-PRP group (77.60; SD, 11.88) improved further than the CSI group (65.72; SD, 15.28; P = .0003). Twenty-seven patients were deemed to have failed the CSI treatment at 16 to 24 weeks, with an exit score of 59.22 (SD, 11.54), and then had treatment with LR-PRP. The crossover group improved with the LR-PRP: from 59.22 (SD, 11.22) at baseline to 75.55 (SD, 16.05) at 12 weeks, 77.69 (SD, 15.30) at 24 weeks, and 77.53 (SD, 14.54) at 104 weeks. The LR-PRP group retained 38 of 39 patients to 52 weeks and continued to improve. Their baseline scores of 53.77 (SD, 12.08) improved to 82.59 (SD, 9.71) at 104 weeks ( P < .0001). Conclusion: Among patients with chronic gluteal tendinopathy and a length of symptoms >15 months, a single intratendinous LR-PRP injection performed under ultrasound guidance results in greater improvement in pain and function than a single CSI. The improvement after LR-PRP injection is sustained at 2 years, whereas the improvement from a CSI is maximal at 6 weeks and not maintained beyond 24 weeks. Registration: ACTRN12613000677707 (Australian New Zealand Clinical Trials identifier).